TARP and Market Discipline: Evidence on the Moral Hazard Effects of Bank Recapitalizations - Jens Forssbaeck; Caren Yinxia Nielsen (Lund University, School of Economics and Management, Department of Economics, 2016)
We examine the moral hazard effects of bank recapitalizations by assessing the impact of the U.S. TARP program on market discipline exerted by subordinated debt-holders using a sample of 123 bank holding companies over the period 2004-2013. Predicted distress risk has a consistently positive and significant effect on sub-debt spreads, suggesting the presence of market discipline. A higher bailout probability significantly reduces the risk-sensitivity of spreads for the full sample, indicating a moral hazard effect of recapitalizations. This appears to be a too-big-to-fail effect, as it is absent when the largest banks are dropped from the sample. Results indicate that it is transitory. We also find a large effect of the crisis, appearing both as a uniform rise in, and a heightened risk sensitivity of, sub-debt spreads during the crisis.
Keywords: E50; G01; G21; G28; H12; 330; Bank bailouts; moral hazard; distress risk; capital injections; TARP; CPP; market discipline; financial crisis